Forsvar for evnen til at være ensom - Marquard, Odo (Slagmark - Tidsskrift for idéhistorie, 2018)
The essay “Forsvar for evnen til at være ensom” (Defense of the capability of being alone) is a critical examination of the growing solitude in modern society. On basis of the assumption that modern age is the age of loneliness, Marquard claims that the problem for modern man is not loneliness in itself, but rather the decreasing capability of being alone. What haunts human beings in modern society is not the increase of solitude but the fact that they become still more unable to experience loneliness in a positive way. Marquard in his essay suggests different forms of such positive experience of loneliness and defends the claim that loneliness is not first and foremost a burden, but rather a fundamental human need.